2021
DOI: 10.1097/nmd.0000000000001356
|View full text |Cite
|
Sign up to set email alerts
|

Attached to Virtual Dreams

Abstract: Maladaptive daydreaming describes excessive fantasy activity that interferes with an individual's life. Surprisingly, the precursors of maladaptive daydreaming and its role in excessive involvement in virtual worlds have been scarcely investigated. In the current study, we examined the relationships among attachment styles, maladaptive daydreaming, and problematic social media use (PSMU) in a sample of community-dwelling adults. Eight hundred seventy-seven participants between 18 and 68 years old were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 97 publications
2
7
0
Order By: Relevance
“…Individuals who experienced frequent maladaptive daydreaming tended to show high anxiety, while individuals who experienced normal daydreaming tended to have secure attachment styles (Mariani et al, 2021;Sándor et al, 2021). The relationship between attachment style and problematic social media use was significantly mediated by maladaptive daydreaming in high anxiety-related styles, but not in the secure style (Costanzo et al, 2021). These results indicate that individuals with an insecure attachment style show a greater 1 Although existing literature using four attachment styles is prevalent (e.g., Brennan et al, 1998), some previous studies have identified three clusters consisting of secure, anxious, and avoidant styles from empirical data (e.g., Ceglian and Gardner, 2001;Kawamoto, 2016).…”
Section: Attachment Style As a Potential Moderator Of The Relationshi...mentioning
confidence: 93%
See 1 more Smart Citation
“…Individuals who experienced frequent maladaptive daydreaming tended to show high anxiety, while individuals who experienced normal daydreaming tended to have secure attachment styles (Mariani et al, 2021;Sándor et al, 2021). The relationship between attachment style and problematic social media use was significantly mediated by maladaptive daydreaming in high anxiety-related styles, but not in the secure style (Costanzo et al, 2021). These results indicate that individuals with an insecure attachment style show a greater 1 Although existing literature using four attachment styles is prevalent (e.g., Brennan et al, 1998), some previous studies have identified three clusters consisting of secure, anxious, and avoidant styles from empirical data (e.g., Ceglian and Gardner, 2001;Kawamoto, 2016).…”
Section: Attachment Style As a Potential Moderator Of The Relationshi...mentioning
confidence: 93%
“…This might be because daydreaming about marital partners was only a way of compensation for individuals with insecure attachment styles. Individuals who display frequent maladaptive daydreaming, which is associated with insecure attachment styles (Costanzo et al, 2021;Mariani et al, 2021;Sándor et al, 2021), tend to address unmet emotional needs by engaging in compensatory fantasies specific to personality traits (Brenner et al, 2022). If partner-related daydreaming served the sole purpose of compensation in individuals with insecure attachment styles, it would be reasonable that the time spent daydreaming did not reflect in the relationship.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The RQ has been shown to possess good test-retest reliability and discriminant validity [ 48 , 49 ] and has been successfully used in research focusing on internet-mediated problematic behaviors [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surveys suggest that particular kinds of mental illness and symptoms, such as self-harm and suicidal ideation, may be heightened by exposure to related content online (Arendt et al, 2019). Relevant to DID, social media usage has been connected to escapism and maladaptive daydreaming (i.e., Costanzo et al, 2021; Kırcaburun & Griffiths, 2019), especially during COVID-19 (Fernandes et al, 2020; Wulf et al, 2022). TikTok should thus be approached not just as a venue through which identity work and communities around mental illness are sustained, but also as an agent that interacts with the mental health of the individuals who use the platform.…”
Section: Dissociative Identity Disordermentioning
confidence: 99%